2004
DOI: 10.1177/0886260504265619
|View full text |Cite
|
Sign up to set email alerts
|

Battered Women’s Perceptions of Risk Versus Risk Factors and Instruments in Predicting Repeat Reassault

Abstract: This study partially replicates and expands on a previous study that showed women's perceptions of risk to be a strong predictor of reassault among batterers. The current study employed a larger and multisite sample, a longer follow-up period of 15 months, and multiple outcomes including "repeated reassault" (n = 499). According to the multinomial logistic regressions, women's perceptions of risk improved prediction with risk factors (ROC area under the curve improved by.04 and sensitivity of repeated reassaul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
132
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(140 citation statements)
references
References 30 publications
5
132
1
2
Order By: Relevance
“…Evaluation of US Risk Assessments Campbell's Danger Assessment has been independently tested in two studies (Bennett et al 2000 andHeckert andGondolf 2004). There was some predictive validity for re-assault, rather than lethality, but there was also a high rate of false positives.…”
Section: Earlier Studies On Prior Record Of Domestic Abuse Predictingmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of US Risk Assessments Campbell's Danger Assessment has been independently tested in two studies (Bennett et al 2000 andHeckert andGondolf 2004). There was some predictive validity for re-assault, rather than lethality, but there was also a high rate of false positives.…”
Section: Earlier Studies On Prior Record Of Domestic Abuse Predictingmentioning
confidence: 99%
“…Yet the evaluation of risk assessment tools is also in its infancy. While risk factors have been identified, their accuracy in terms of predictions has been low, with many false positives and false negatives (Heckert and Gondolf 2004). A risk assessment approach known as SPECSS+ (Separation, pregnancy, escalation, community issues, stalking and sexual assault) was introduced in most forces including Thames Valley during 2005 and.…”
Section: Introductionmentioning
confidence: 99%
“…2008; Heckert & Gondolf, 2004;Hilton, et al, 2004), as is the effect of separation or the threat of separation on DA (Weisz, Tolman, & Saunders, 2000).…”
Section: Running Head: Individual Predictive Validity Of the Uk's DV mentioning
confidence: 99%
“…A nationwide survey on domestic violence in Norway found that 10% of the women and 2% of the men had experienced severe IPV (Haaland et al 2005). Recent reviews of IPV have emphasized that there is a paucity of studies on violence escalation and interaction, dynamics of violence, and prediction and coping of IPV incidents as perceived and experienced by the target of violence (Langhinrichsen-Rohling 2005;Schwartz 2005;Arriaga and Capezza 2005;Cano and Vivian 2001;Heckert and Gondolf 2004;Mears and Visher 2005;MessmanMoore and Long 2003;Winstok 2007). The research we are reporting here was initiated to address four main researches of the experiences of 157 women: (1) their responses to violence escalation and violence perpetrated by the partner, (2) the effect of pregnancy and motherhood on IPV, (3) thebefore, during and after the IPV; dynamics of violence; effect of alcohol and drug intoxication; and revictimization.…”
Section: Introductionmentioning
confidence: 99%